Implant rehabilitation in fibula-free flap reconstruction: A retrospective study of cases at 1–18 years following surgery. Issue 10 (October 2017) - Sozzi, Davide; Novelli, Giorgio; Silva, Rebeka; Connelly, Stephen T.; Tartaglia, Gianluca M.
Abstract: Purpose: To determine the dental implant and prostheses success rate in a cohort of patients who underwent a vascularized fibula-free flap (FFF) for maxillary or mandibular reconstruction. Methods: The investigators implemented a retrospective cohort study composed of patients who had undergone primary or secondary FFF reconstruction jaw surgery plus placement of 2–6 implants in the reconstructed arch, which were restored with an implant-supported prosthesis. The sample was composed of all patients who underwent FFF surgery between 1998 and 2012 and had either simultaneous or secondary dental implant placement. A total of 28 patients met inclusion criteria. Of these, 22 patients participated in the retrospective review. Patients were examined by an independent observer between January-December 2015. In addition, all patients completed a questionnaire to access satisfaction with the implant-supported prosthesis. Results: The patient cohort consisted of 12 males and 10 females, age 12–70 years. A total of 100 implants were placed, 92 implants in fibular bone and 8 implants in native bone. In the maxilla, 35 implants were placed into fibular bone and 4 into native bone (11 in irradiated patients and 28 in non-irradiated patients). In the mandible, 57 implants were placed into fibular bone and 4 into native bone (15 in irradiated patients and 46 in non-irradiated patients). The mean follow-up after implant loading was 7.8 years (range 1.3–17.5 years). The implant survival rate was 98% (95% CI: 92.2%–99.5%). No statistically significant difference was found in implant success between maxillary and mandibular implants, or between radiated and non-radiated bone. The prostheses success rate, determined by clinical exam and patient satisfaction, was 100%. Conclusion: The results of this study suggest that implant survival is high and implant-supported prostheses are a reliable rehabilitation option in patients whose jaws have been reconstruction with a FFF.